Ability to detect and identify the presence of particles influences consumer acceptance of yoghurt. (October 2020) - Olarte Mantilla, Sandra M.; Shewan, Heather M.; Shingleton, Rebecca; Stokes, Jason R.; Smyth, Heather E.
Highlights: Yoghurt consumer acceptance is influenced by particle detection. Particle concentration, followed by modulus, were key drivers of reduced acceptance of yoghurt. Sensory detection threshold for particles in yoghurt related to size, hardness and concentration. Abstract: The common practice of particle addition into semisolid foods is known to influence sensory textural properties, but the resulting influence on consumer acceptability is not well understood. A systematic trial was therefore designed, involving a set of nine yoghurt samples, to investigate the effect of particle addition on consumer acceptability. Agar microgels were fabricated and added to yoghurt at varying levels of modulus (210 kPa or 550 kPa, fabricated with 5% or 10% agar, respectively), particle size (30 μm or 100 μm) and particle concentration (2% or 5%, w/w). The yoghurt samples were presented to consumers (n = 117), who rated acceptability, and subsequently selected from the attributes particles, drying, sweet, smooth, no particles and none of these by 'check all that apply' (CATA), for each sample. On average, all samples were generally well-liked by consumers, although samples containing 5% (w/w) particles were less acceptable than those containing 2% (w/w) particles. Consumer cluster analysis was used to identify groupings of consumers based on difference in acceptability scores. Acceptability scores for the yoghurts were lower for the consumers who selected the attribute particles in the higher modulus samples. Addition of particles (30 μm or 100 μm) at 550 kPa modulus and 5% (w/w) particles was identified as the threshold of particle detection in this yoghurt system and the point at which acceptability scores declined.